Aktualisasi Operasional BMT UGT Sidogiri Jember Dalam Memajukan Perekonomian Masyarakat - Supandi, Ach Faqih; Hannan, Fais Faizul; Azakia, Kiki; Umbara, Bastomi Dhani (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The Indonesian economy is currently growing and developing. This can be seen from the number of financial institutions that continue to maintain their viability in the face of competition. Indonesian financial institutions are usually traditional financial institutions, but currently there are many sharia-based financial institutions. One institution or business entity that is suitable to overcome this problem is the integrated independent business center or better known as Baitul Maal Wat Tamwil (BMT). This research uses quantitative methods to conduct descriptive and qualitative research. Moleong explained, by using descriptive and qualitative methods, the data collected was in the form of text, images, not digital data. This data can be obtained from interviews, field notes, videos, photos and personal documents. The results of this research are that Baitul Maal wa Tamwil (BMT) is a microfinance institution organized by a sharia microfinance institution which is run with the concept of profit sharing, developing sharia microenterprises which aim to raise the status and dignity and defend the interests of the community. poor and destitute people. disadvantaged community groups. BMT has quite a big opportunity based on the concept of justice and is in line with sharia law.